Some mercurial resistance plasmids from different incompatibility groups specify merR regulatory functions that both repress and induce the mer operon of plasmid R100 - FOSTER, TIMOTHY (My University, 1985)
Transcription of the mer genes of plasmid R100 is regulated by the product of the merR gene. The merR gene negatively regulates its own expression and also controls the transcription of the merTCA operon both negatively (in the absence of inducer) and positively (in the presence of inducer). We used transcriptional mer-lac fusions of R100-1 in complementation tests to measure the ability of the merR products of different mercury-resistant transposons and plasmids to functionally interact with R100-1. Plasmids from incompatibility groups C, B, S, L, and P, as well as the Pseudomonas transposons Tn501 and Tn3401, regulated the expression of the R100 mer genes in a similar fashion to the R100-1 merR product itself, suggesting that these elements are closely related. Only plasmid R391 (IncJ) did not complement.